Benfotiamine Counteracts Smoking-Induced Vascular Dysfunction in Healthy Smokers - Alin Stirban; Simona Nandrean; Stanley Kirana; Christian Götting; Ioan Andrei Veresiu; Diethelm Tschoepe (International Journal of Vascular Medicine)
Background. Smoking induces endothelial dysfunction (ED) mainly by exacerbating oxidative stress (OS) and inflammation. Benfotiamine, a thiamine prodrug with high bioavailability, prevents nicotine-induced vascular dysfunction in rats. It remained unknown whether this effect also occurs in humans. Methods. Therefore, 20 healthy volunteers (mean age: 38 years) were investigated twice, 7–10 days apart in a randomized, cross-over, and investigator-blinded design. Vascular function was assessed by flow-mediated vasodilatation (FMD) of the brachial artery and by measurements of the soluble vascular cell adhesion molecule (sVCAM)-1. Investigations were performed after an overnight fast as well as 20 minutes after one cigarette smoking. On another day, the same procedure was applied following a 3-day oral therapy with benfotiamine (1050 mg/day). Ten patients were randomized to start with smoking alone, and ten started with benfotiamine. Results. Results are expressed as (mean ± SEM). Smoking acutely induced a decrease in FMD by 50% (∗∗P<0.001 versus baseline) an effect significantly reduced by benfotiamine treatment to 25%∗§ (∗P<0.05 versus baseline, §P<0.05 versus smoking alone). Smoking-induced elevation in sVCAM-1 was also prevented by benfotiamine. The endothelium-independent vasodilatation remained unaltered between days. Conclusion. In healthy volunteers, smoking blunts vascular function mirrored by a decrease in FMD and an increase in sVCAM-1. Short-term treatment with benfotiamine significantly reduces these effects, showing protective vascular properties.